2022
DOI: 10.1002/smm2.1149
|View full text |Cite
|
Sign up to set email alerts
|

Insights into enhanced electrochemiluminescence of a multiresonance thermally activated delayed fluorescence molecule

Abstract: The electrochemiluminescence (ECL) behavior of a multiresonance thermally activated delayed fluorescence molecule has been investigated for the first time by means of ECL-voltage curves, newly designed ECL-time observatory, and ECL spectroscopy. The compound, Mes 3 DiKTa, shows complex ECL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…More recently, several reports have documented organic long-persistent luminescent compounds whose luminescence decays in the order of seconds. , The long-lived luminescence in this class of emitters originates from charge separation, followed by a slow charge recombination route, often in a framework of electron-donating and electron-accepting molecules to facilitate the formation of charge-separated states . This phenomenon has been reported for photoluminescent materials (OLPL), but also recently by us for electrochemiluminescence (OLECL). , In particular, there is evidence that the compounds that exhibit organic long-persistent luminescence often possess aggregate excited states …”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…More recently, several reports have documented organic long-persistent luminescent compounds whose luminescence decays in the order of seconds. , The long-lived luminescence in this class of emitters originates from charge separation, followed by a slow charge recombination route, often in a framework of electron-donating and electron-accepting molecules to facilitate the formation of charge-separated states . This phenomenon has been reported for photoluminescent materials (OLPL), but also recently by us for electrochemiluminescence (OLECL). , In particular, there is evidence that the compounds that exhibit organic long-persistent luminescence often possess aggregate excited states …”
Section: Introductionmentioning
confidence: 89%
“…40 This phenomenon has been reported for photoluminescent materials (OLPL), 41 but also recently by us for electrochemiluminescence (OLECL). 16,42 In particular, there is evidence that the compounds that exhibit organic longpersistent luminescence often possess aggregate excited states. 43 Recently, the synthesis and photophysical properties of a series of through-space charge transfer thermally activated delayed fluorescence compounds 4,4′-(1,2-dihydroacenaphthylene-5,6-diyl)bis(N,N-diphenylaniline) (TPA-ace-TRZ) (Figure 1A), 4-(1,2-dihydroacenaphthylen-5-yl)-N,N-diphenylaniline (TPA-ace) (Figure 1B), 6-(4-(diphenylamino)phenyl)-1,2-dihydroacenaphthylene-5-carbonitrile (TPA-ace-CN) (Figure 1C), and 4,4′-(1,2-dihydroacenaphthylene-5,6diyl)bis(N,N-diphenylaniline) (2TPA-ace) (Figure 1D) were first investigated by us.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, some progress has been achieved in the topic of TADF-ECL, such as the achievements of highly efficient TADF-ECL in organic medium [ 18 , 19 , 29 , 30 , 31 ], extremely narrow ECL spectra [ 32 ], reliable TADF-ECL in aqueous medium [ 12 , 33 ] and TADF-ECL sensing applications [ 19 , 34 ]. In 2014, Ishimatsu et al reported the first annihilation TADF-ECL, in which a TADF molecular 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN) [ 35 ] was used as the ECL luminophore in organic medium [ 18 ].…”
Section: Introductionmentioning
confidence: 99%